Extensive Lysine Methylation in Hyperthermophilic Crenarchaea: Potential Implications for Protein Stability and Recombinant Enzymes. (19th July 2010) - Botting, Catherine H.; Talbot, Paul; Paytubi, Sonia; White, Malcolm F.
Abstract : In eukarya and bacteria, lysine methylation is relatively rare and is catalysed by sequence-specific lysine methyltransferases that typically have only a single-protein target. Using RNA polymerase purified from the thermophilic crenarchaeum Sulfolobus solfataricus, we identified 21 methyllysines distributed across 9 subunits of the enzyme. The modified lysines were predominantly inα -helices and showed no conserved sequence context. A limited survey of the Thermoproteus tenax proteome revealed widespread modification with 52 methyllysines in 30 different proteins. These observations suggest the presence of an unusual lysine methyltransferase with relaxed specificity in the crenarchaea. Since lysine methylation is known to enhance protein thermostability, this may be an adaptation to a thermophilic lifestyle. The implications of this modification for studies and applications of recombinant crenarchaeal enzymes are discussed.